From clicks to carts: How social media shapes food purchase behaviour in Klang Valley - Kori, Nur Liana; Mohd Salleh, Mohammad Zaim; Mat Alini, Syukrina Alini; Saiful Bahry, Norliza; Mat, Azmi (Universiti Teknologi Mara Selangor, 2025)
The study investigates the impact of social media on food purchasing behavior in Klang Valley, Malaysia, emphasizing hashtags, social media influencers, and culinary festivals. Data were gathered using a quantitative research approach using an online survey administered to 100 respondents selected via convenience sampling. The results indicate that social media influencers and food festivals significantly influence consumer food purchasing behaviour, whereas hashtags exhibit no significant direct effect. The regression model accounted for 57.9% of the variance in purchase behaviour, highlighting the significance of credibility and experiential involvement in customer decision-making. These results indicate that although hashtags increase visibility, they serve mainly as discovery instruments rather than persuasive strategies. Conversely, influencers and culinary festivals act as significant catalysts for trust, engagement, and purchasing intentions. The research indicates that food marketers have to emphasize partnerships with influencers and experiential platforms while using hashtags as ancillary tactics. Future studies may investigate cultural differences, long-term consequences, and innovative technology like AI-driven customization and virtual reality in influencing customer behavior.